Pain in sickle cell diseases; physicians’ knowledge, attitude, and barriers: a cross sectional study - Aljuhani, Ohoud (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the status of acute pain management in sickle cell disease patients, and to explore the association between professional experience and therapeutic preferences among the physicians for the management of sickle cell disease-related acute pain management. Method: The cross-sectional study was conducted from June to September 2018 and comprised physicians from 20 hospitals across Saudi Arabia. Data was collected using a 13-item survey form investigating physicians’ general information and related barriers regarding acute pain management in sickle cell disease patients. Data was analysed using SPSS 25. Results: Of the 300 individuals approached through emails, 201(67%) responded. There were 122(61%) males and 78(39%) females; 126(63%) had experience <5 years, while 41(20%) had experience >10 years; the largest group of physicians belonged to Internal Medicine 46(23%); 41(20.4%) came across sickle cell disease patients ‘very often' and 31(15.4) had never come across such a patient. There was no significant association between professional experience and therapeutic management preferences (p>0.05). Conclusion: Physicians’ knowledge, attitude and practice related to acute pain management in sickle cell disease patients was adequate. More awareness is needed for optimal management of pain in such patients. Key Words: SCD, Sickle cell disease, Opioids, Acute pain, Physicians.